THE GREEN ELECTRICITY MARKET Analyzing how the UK can improve upon its green policies by learning from the US - Deshwal, Saru (2007)
Globally, the energy consumption is increasing at a rapid rate. The World Energy Outlook (2007) predicts that in the next 25 years, energy consumption will increase by 60 percent with the bulk of this growth to occur in developing countries. This bears testimony to the fact that global energy sustainability concerns are very much the 'Third World War' of today. However in this case, instead of countries fighting against each other, they need to fight together for the environment. In order to combat CO2 emissions and scarcity of non-renewable energy supplies, regulatory bodies in the United Kingdom (UK) and the United States (US) have designed policies revolving around the 'green' issue and this report particularly compares the policies under both countries and ultimately assesses what the UK can learn from its US counterpart in terms of greening the energy market.